JAVA ETHNICITY OF THE FEMINISM GOVERNANCE, SUSTAINABILITY POLICY, AND FINANCIAL STABILITY - WIDYATAMA, ARIF (Program Studi Akuntansi Universitas Islam Lamongan, 2024)
This study examines the relationship between Feminism Governance, Javanese Ethnicity, and its impact on Financial Stability and Investor Judgment. This concept is based on the characteristics of CEOs and Commissioners, including gender and Javanese ethnicity. This article uses a literature review to explain the relationship between the Javanese ethnicity of female CEOs and its relationship to financial stability and investor judgment. The results of this article show that both female CEOs and commissioners with a Javanese ethnic background will prefer to focus on and implement sustainability policies for companies that consist of social, environmental, and governance. This sustainability policy will ultimately increase the company's long-term profits. A good sustainability policy for a company increases the company's financial stability in the long term. The good financial stability of a company can make investors see the company as good, thus making investors behave in making decisions to invest in the company. This article is the first to discuss Javanese ethnicity in CEOs and company commissioners, previously many articles only discussed the gender composition of CEOs and commissioners.